SOSIALISASI PROTOKOL KESEHATAN PENCEGAHAN PENYEBARAN COVID-19 DI ERA NEW NORMAL - Estriana Murni Setiawati; Sriyati (Stikes Yarsi Mataram, 2023)
New normal is a change in behavior to prevent transmission of COVID-19 in carrying out or carrying out normal activities by implementing health protocols. Growing self-awareness of the importance of complying with health protocols is very important. Therefore it is necessary to socialize health protocols in the New Normal Era in the form of health education on hand washing moments along with proper hand washing procedures, the importance of wearing masks, and maintaining distance in public spaces. This service program aims to increase knowledge to prevent an increase in COVID-19 cases in the New Normal Era. This service is carried out by holding counseling about the importance of wearing masks and keeping a distance in public places as well as demonstrations of good and proper hand washing with the number of respondents being 30 residents. Evaluation is carried out by giving pre-test and post-test socialization material with an instrument in the form of an assessment check list. The stages of implementation of activities include the preparation, implementation and evaluation of reporting. Socialization activities are carried out at the homes of community leaders when there are community agendas using leaflets and demonstrations. This is done so that people can learn through direct practice and see examples from leaflet media. The results of the dedication show an increase in residents' knowledge of health protocol socialization material by showing an increase in the results of the pre-test and post-test given